Structures of Small Fen-1Ni(n = 2-7) Clusters: A Density Funcational Theory Study - Yu, Shuaiqin; Jia, Xiangfeng; Dong, Lihua; Yin, Yansheng (Asian Journal of Chemistry, 2010)
All possible geometrical structures of Fen-1Ni(n = 2-7) clusters were optimized at the BPW91 level in density functional theory. Theoretical results show that the Ni atom prefers to occupy the surface site and does not change the frame structures of iron atoms. Further, we analyze the stability of the lowest-energy structures for Fen-1Ni(n = 2-7) clusters and the corresponding results of the second difference in energy, the vertical ionization potential as well as the HOMOLUMO energy gap show that the Fe5Ni has special stability.